Les modeles economiques des associations sportives: Le cas des clubs de handball du nord de la France - Janssoone, P.-Y.; Feuillet, A.; Jeöl, M.; Terrien, M. (Management & Organisations du Sport, 2022)
The French Handball Federation has put at the heart of its strategic project the aim to see its clubs diversifying their financial resources and increasing their participation services (health, leisure...) to remain attractive in a changing sport context. To accompany this process, this research focuses on the economic models of handball clubs to categorize them and identify development levers. Different statistical methods were applied to achieve this. A principal component analysis and a K-means classification allow the authors to propose a double taxonomy of clubs based on their economic models and their level of professionalization. These methods were applied to the results from a questionnaire sent to the 59 clubs of the Comité Nord, and from which 49 responded. The framework produced allows to characterize the current situation of the French handball clubs and to identify different opportunities and threats for each of the identified categories.